2018
DOI: 10.1021/acs.est.8b00778
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Ozone in the Eastern U.S. using a Fuel-Based Mobile Source Emissions Inventory

Abstract: Recent studies suggest overestimates in current U.S. emission inventories of nitrogen oxides (NO = NO + NO). Here, we expand a previously developed fuel-based inventory of motor-vehicle emissions (FIVE) to the continental U.S. for the year 2013, and evaluate our estimates of mobile source emissions with the U.S. Environmental Protection Agency's National Emissions Inventory (NEI) interpolated to 2013. We find that mobile source emissions of NO and carbon monoxide (CO) in the NEI are higher than FIVE by 28% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
77
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 69 publications
(133 reference statements)
8
77
2
Order By: Relevance
“…The agreement of decreasing trends among the datasets is just as good for the post-2011 period as the pre-2011 period. This result differs from Miyazaki et al (2017) and Jiang et al (2018), who suggested no significant decreasing trend for OMI TVCD data and inversed NO x emissions after 2010. The disagreement can be explained by the results of Fig.…”
Section: Trend Analysis Of Aqs No 2 Surface Concentrationscontrasting
confidence: 98%
See 4 more Smart Citations
“…The agreement of decreasing trends among the datasets is just as good for the post-2011 period as the pre-2011 period. This result differs from Miyazaki et al (2017) and Jiang et al (2018), who suggested no significant decreasing trend for OMI TVCD data and inversed NO x emissions after 2010. The disagreement can be explained by the results of Fig.…”
Section: Trend Analysis Of Aqs No 2 Surface Concentrationscontrasting
confidence: 98%
“…The continuous decrease in anthropogenic NO x emissions was consistent with the ongoing reduction in vehicle emissions (McDonald et al, 2018). On the other hand, Miyazaki et al (2017) and Jiang et al (2018) found that the US NO x emissions derived from satellite NO 2 TVCDs, including OMI (the Ozone Monitoring Instrument), SCIA-MACHY (SCanning Imaging Absorption SpectroMeter for Atmospheric CHartography), and GOME-2A (Global Ozone Monitoring Experiment 2 onboard METOP-A), were almost flat from 2010-2015 and suggested that the decrease in NO x emissions was only significant before 2010, which was completely different from the bottom-up and fuel-based emission estimates.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations